2.4 GHZ QPSK demodulator using MATLAB - Farihah Salleh @ Hashim
The goal of this final year project is to design and implement QPSK Modulator. The design consisted of one major section which is QPSK Modulator. The general ideas for this project is to study the transmission process and to design the modulation system.